Infrastructure Grants and the Performance of Microenterprises - Ritam Chaurey; Duong Trung Le (Institute of Labor Economics (IZA), 2018)
We evaluate the impact of a place-based infrastructure development scheme directed towards India's most "backward" districts, on the performance of microenterprises. "Backward" districts were selected based on a transparent score-based assignment mechanism. Using a Fuzzy Regression Discontinuity Design, we find that firms in treated districts had higher profits, revenues, and employment. Improvements in electrification was an important channel driving these results, as firms used more electricity and had a lower likelihood of facing a power cut. We also find increases in migrants, and proportion of new firms in treated districts, along with negative spillovers in areas closer to the treated districts.
Keywords: O12; O18; O25; R11; 330; infrastructure; microenterprises; place-based policy; regression discontinuity